Community care and the fundholder. Issue 6878 (6th March 1993) - Morris, R
Abstract : According to the government, clearly agreed local arrangements should enable individual general practitioners to make their full contribution to the new system of community care without getting involved in extra bureaucracy. From 1 April the main part of that contribution will be to refer to social services those patients who seem to need social care. Many general practitioners are worried that such referrals will be complex and time consuming and will generate too much extra work. Moreover, general practitioners may also be asked to see patients specifically to help social workers' assessment procedures, and many fear that such consultations will overwork and underpay them. General practitioner fundholders already use contracts to spell out what they expect from hospital services. From 1 April they will be able to set up contracts for community health services such as district nursing and chiropody, and possibly this might be extended to social aspects of community care. Over the past 14 months Dr Rhidian Morris and his partners in a fundholding practice in Devon have piloted contracts for all aspects of community care. In this article Dr Morris explains how the most radical part of the pilot project–the contract for social care–was set up. He argues that the lessons on communication that came from what was essentially a fundholding project could apply also to non-fundholding practices.